Distrust in Banks and Fintech Participation: The Case of Peer-to-Peer Lending. (September 2022) - Saiedi, Ed; Mohammadi, Ali; Broström, Anders; Shafi, Kourosh
What has boosted crowdfunding's growth? In the case of peer-to-peer (P2P) lending, we highlight the role of consumers' distrust in banks. We offer evidence that distrust in banks likely triggers individuals to supply funding toward crowdfunding and away from bank deposits. We highlight that a distrust mindset promotes questioning default choices and considering alternatives, and fosters comparisons focusing on dissimilarities. Our findings suggest US states whose residents express greater distrust in banks are more likely to fund P2P loans and, conditional on funding, lend higher amounts. This relationship is more pronounced when funding small loans or borrowers with less banking access.